Clinical Outcomes among HIV/Tuberculosis-Coinfected Patients Developing Immune Reconstitution Inflammatory Syndrome after HAART Initiation in South India. (February 2013) - Kumarasamy, N.; Venkatesh, Kartik K.; Vignesh, R.; Devaleenal, B.; Poongulali, S.; Yepthomi, Tokuga; Flanigan, Timothy P.; Benson, Constance; Mayer, Kenneth H.
Introduction: We determine the frequency and immunological outcome of developing immune reconstitution inflammatory syndrome (IRIS) among HIV/tuberculosis (TB)–coinfected Indians receiving highly active antiretroviral therapy (HAART). Methods: Patients coinfected with TB and HIV who initiated HAART were classified based on treatment outcomes (IRIS and non-IRIS) utilizing an observational HIV/AIDS cohort. Results: A total of 1731 HIV/TB-coinfected patients initiated HAART, and 95 of these patients (5.5%) developed TB-IRIS, with an incidence rate of 0.26 per 100 person-years. Patients who developed IRIS had significantly higher CD4 counts than non-IRIS patients at the time of initiating HAART, as well as after 6 months, 18 months, and 24 months following HAART initiation ( P < .05). Conclusions: HIV/TB-coinfected patients who developed IRIS following HAART initiation had equivalent clinical outcomes compared with their HIV/TB-coinfected counterparts who did not develop IRIS, suggesting minimal long-term risks associated with IRIS.